(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
Telehealth seems to be the new normal in this fast-changing environment. According to the European Commission eHealth was among the highest priorities before the COVID -19 pandemic. Transformation of health and care in the digital single market is among the EU`s six political priorities of the Commission 2019-2024 (2018 Communication on Digital Health and Care). The pandemic caused by COVID-19 just accelerates the necessity of the inclusion of digital health into the traditional healthcare systems. Telehealth services are among the biggest eHealth trends in EU. Therefore, one of the challenges is the national, regional and regulatory priorities regarding telehealth. There is lack of telehealth special legislative and governmental policies that needs to stimulate the developing and innovative solutions in medicine through technology and to envisage the upcoming innovation technology. Therefore, the government support and adequate policy making is important to support the development of the telehealth services. One of the main challenges is the electronic transactions of patient data among the telehealth providers and services and the cross-border patient data share. Another issue is the exchange of information among the national health institutions and providers and their interoperability. The Macedonian legislation does not have special legislation (policies, or laws) about telehealth. Telehealth is regulated as a term in the Law on health protection. Additionally, there is a lack of national acts, literature, and research in this subject matter. Thus, this paper will explore the telehealth from two main perspectives: scientific theories and legal practice and the users’ practice. Hence, this paper will analyze the legislation about the telehealth on the EU level and the EU Member States and the Macedonian legislation and the impact on the e-health that was made during COVID-19 pandemic. Furthermore, it will make comparative analyses among different countries into the EU zone compared with the EU aspirant country- the Republic of North Macedonia. A survey conducted among doctors in private and public healthcare institutions in the primary, secondary, and tertiary healthcare levels in the city of Stip and in the city of Skopje will provide data about the challenges, risks, and trends in telehealth before and during COVID -19.